2001
DOI: 10.1007/pl00011251
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Characteristics of 28 Patients with Staphylococcus schleiferi Infection

Abstract: The aim of this study was to analyse the clinical and microbiological characteristics of a series of patients with infection by Staphylococcus schleiferi. Seventy-one isolates were recovered from 36 patients between January 1993 and June 1999 at a tertiary care centre in northern Spain. There were 28 patients with well-documented clinical data. Infection was more frequent in men (89.3%), and more than half of the patients had some degree of immunosuppression, mainly malignant neoplasms. Infection was nosocomia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 18 publications
0
45
3
7
Order By: Relevance
“…This pathogen expresses a clumping factor, as does S. lugdunensis, and it also displays betahemolysin activity that may be responsible for its erroneous identification as S. aureus in the routine laboratory setting (37,40). Clinical reports that describe infections with this pathogen remain scarce, although they appear unusual in their presentation and severity for a CoNS-mediated infection (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathogen expresses a clumping factor, as does S. lugdunensis, and it also displays betahemolysin activity that may be responsible for its erroneous identification as S. aureus in the routine laboratory setting (37,40). Clinical reports that describe infections with this pathogen remain scarce, although they appear unusual in their presentation and severity for a CoNS-mediated infection (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…This pathogen expresses a clumping factor, as does S. lugdunensis, and it also displays betahemolysin activity that may be responsible for its erroneous identification as S. aureus in the routine laboratory setting (37,40). Clinical reports that describe infections with this pathogen remain scarce, although they appear unusual in their presentation and severity for a CoNS-mediated infection (40,41). The production of a fibrinogen affinity factor might be involved in colonization of the vascular endothelium, one of the primary events in the pathogenesis of infective endocarditis, and its implication has been reported in experimental models of endocarditis (42).…”
Section: Discussionmentioning
confidence: 99%
“…Little attention has been paid to S. schleiferi in people outside of reports of outbreaks or individual cases (Freney et al, 1988; Vandenesch et al, 1994; Kluytmans et al, 1998; Hernandez et al, 2001; Kumar et al, 2007; Tzamalis et al, 2013). Although some reports have focused on surgical site infections, including those associated with pacemakers, others demonstrate a wider variety of sources, including wound or eye infections and meningitis (Hernandez et al, 2001; Tzamalis et al, 2013).…”
mentioning
confidence: 99%
“…Various human cases have been described including wound infection, prosthetic infections, and bacteremia (Celard et al, 1997; Da Costa et al, 1998; Freney et al, 1988; Hernandez et al, 2001; Igimi et al, 1990; Kumar et al, 2007; Latorre et al, 1993; Vandenesch et al, 1994). A review of 28 cases in the literature in 2001, reported that all isolates were coagulase negative: 50% of cultures were from wound infections, 19.4% were found in blood cultures, 13.8% from catheter tips, 8.3% from ear exudates, and 5.5% from cerebrospinal fluid.…”
Section: Case Reportmentioning
confidence: 99%
“…A review of 28 cases in the literature in 2001, reported that all isolates were coagulase negative: 50% of cultures were from wound infections, 19.4% were found in blood cultures, 13.8% from catheter tips, 8.3% from ear exudates, and 5.5% from cerebrospinal fluid. Other sites, each with one case, included pleural fluid, corneal exudate, biliary drainage and urine (Hernandez et al, 2001). S. schleiferi is often mistaken for S. aureus as both express clumping factor and heat stable DNase.…”
Section: Case Reportmentioning
confidence: 99%